[Two students studying in a Red Brick dorm room] (1977)
Two students are sitting on a bed. Posters, including a Snoopy poster and Peanuts calendar, as well as a Smokey Bear poster with a burnt match as the I of 'think', hang on the wall alongside decorations and stuffed animals.